Kebijakan Dan Strategi Partai Nasdem Kota Banda Aceh Dalam Meningkatkan Partisipasi Politik Perempuan - Teuku Ahyar Chehuna; Musda Wati; Fatimahsyam Fatimahsyam (Jurnal Community, 2025)
The issue of women's political participation in Aceh remains low, and the Nasdem Party is attempting to resolve this issue. This study aims to explain the policies and strategies developed by the Nasdem Party in Banda Aceh, as well as the challenges and obstacles faced by the Nasdem Party in Banda Aceh in increasing women's political participation. This study uses a descriptive qualitative approach to explore in depth the policies, strategies, challenges, and obstacles faced by the party in increasing the participation of female cadres to be actively involved in politics. Data was obtained through in-depth interviews, participatory observation, and documentation. The results of the study show that to encourage women's participation in politics, the Nasdem Party has created an affirmative policy requiring 30% female representation in its leadership and legislative candidacy and has developed a strategy to open up wider opportunities for women's participation. However, despite a formal commitment to supporting women's political involvement, the implementation of affirmative policies and participation strategies within the party is still not optimal. Structural barriers, such as weak internal party support and the lack of a sustainable leadership training system, are the main obstacles.